Effect of the Congenital Heart Disease on Growth and Nutritional State of Children - Shuker Alghanimi, Muhannad K; Alyasiri, Adeebah A; Musa, Russul F (Diyala Journal of Medicine, 2018)
Background:This study will show the most likely congenital heart disease that affect on growth parameters which re- arrange our information for rapid referring of such patient to solving their problems and maintains the life of child and decrease burden on salary of family. Objective: To assess nutritional status and factors that predicts nutritional changes in children with congenital heart disease. Patients and Methods: Cross-sectional study, of 110 patients with congenital heart diseases, performed in Al-Hilla and Baghdad cities in Iraq. Children were divided into three groups according to the age. Cardiac diagnosis was made on basis of clinical history, examination, electrocardiography and echocardiography. acute malnutrition assessed by weight/length ratio, chronic malnutrition assessed by length/age ratio, while poor nutritional status and acute deterioration of health status assessed by weight/age ratio. Results: 110 patient; Wasted or severely wasted (60.9%) according to weight/length, and Stunted or severely stunted (61.8%) according to length for age measure; and wasted or severely wasted was (42.7%) according to BMI . There was significant association between acute malnutrition and child age, p value <0.002. Acute malnutrition (Wasted or severely wasted) more with left side volume overload (62.7%) and (60.2%) those with chronic malnutrition (Stunted or severely stunted) have complex heart disease. There was significant association between malnutrition assessed by weight for height and presence of mild, moderate and Severe PHT, absence or presence of treatment, type of feeding and syndromatic type of CHD. There was significant association between chronic malnutrition assessed by height for age and cyanosis, pulmonary hypertension and type of feeding. There was significant association between acute malnutrition assessed by BMI for age and pulmonary hypertension, absence or presence of treatment and type of feeding. There was significant association between malnutrition assessed by Weight for height and history of abortion. Conclusion: Congenital heart disease can affect the growth of children so need resolve these problems by correcting the cardiac abnormality whether by cardiac catheterization of surgical intervention.